Balance Among Cognitive Control Processes: A Case Study of a Gifted Youth. Issue 1 (2nd January 2018) - Urben, Sébastien; Camos, Valérie; Habersaat, Stéphanie; Constanty, Lauriane; Stéphan, Philippe
Abstract : This case study analyzed the cognitive strategies of Ethan, a gifted youth, when performing a Stop Signal Task assessing cognitive control processes including response inhibition as well as proactive and reactive adjustments of response. In the case of Ethan, the response inhibition score was biased, revealing that Ethan did not follow the instructions but challenged them and was successful in doing this. Specifically, he made important proactive adjustments, by both slowing down and speeding up (i.e., risk taking) his responses according to the likelihood of the apparition of the stop signal (triggering response inhibition). Ethan's performance indicated that he perfectly understood the procedure behind the task and completed it according to his own comprehension. Ethan's results showed that researchers and clinicians must be careful when assessing gifted children and adolescents by using tasks that they cannot defeat.